2008
DOI: 10.1007/s11695-008-9477-z
|View full text |Cite
|
Sign up to set email alerts
|

The Eradication of Helicobacter pylori is Affected by Body Mass Index (BMI)

Abstract: Overweight/obese nondiabetic patients showed a significantly lower rate of eradication rate of H. pylori infection than controls. BMI and corpus-predominant gastritis appear to be independent risk factors for eradication failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
4
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 37 publications
1
51
4
5
Order By: Relevance
“…By contrast, lower basal metabolic index (BMI) patients (especially Asian) will have better outcomes [10]. Smoking is another risk factor for failure of therapy.…”
Section: Risk Factorsmentioning
confidence: 99%
“…By contrast, lower basal metabolic index (BMI) patients (especially Asian) will have better outcomes [10]. Smoking is another risk factor for failure of therapy.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The urea breath test uses the fact that H. pylori yields urease, an enzyme that metabolizes urea into ammonia and carbon dioxide (CO 2 ). For this test, patients swallow a tablet that contains a small amount of 13C-labeled urea (Abdullahi et al 2008;Fleming et al 2009). 13C is a nonradioactive form of carbon that is slightly heavier than normal carbon.…”
Section: Noninvasive Testsmentioning
confidence: 99%
“…Abdullahi et al [6] compared 40 overweight/obese patients with 41 normal weight patients in a non-diabetic cohort and suggested that overweight/obese nondiabetic patients showed a significantly lower rate of eradication rate of H. pylori infection than controls, and that BMI and corpus-predominant gastritis appear to be independent risk factors for eradication failure, concluding that alternative treatment regimens with higher dose and/or longer duration may be necessary in obese/overweight patients to achieve a higher eradication rate. However, in our cohort, it was not possible to find differences in eradication rates among the various subgroups according to the BMI, neither dividing patients as obese and nonobese (71 vs. 42 patients), regardless of the duration of treatment.…”
Section: The Impact Of Bmi On H Pylori Eradication Is Debatablementioning
confidence: 99%
“…In the last two decades, several studies have shown strong evidence of some of these factors related to the host that negatively influence the eradication rates, especially polymorphisms in the genes CYP2C19, MDR1, and IL-1, [1][2][3] low compliance, [4] and hypersecretion of hydrochloric acid. [5] However, the evidence is scarce for other factors, particularly the impact biotype, [6] smoking, [7] diabetes mellitus (DM), [8] and previous treatment failure. In particular, it is unknown whether the body mass index (BMI) influences in a clinically significant way the phar macokinetics and/or pharmacodynamics of the drugs involved in eradication (in particular, the proton pump inhibitors and antibiotics).…”
Section: Introductionmentioning
confidence: 99%